THE INFLUENCE OF CUSTOMER EXPERIENCE VALUES ON LOYALTY TO MAKE OVER COSMETIC PRODUCTS IN THE PANTON LABU CITY COMMUNITY, NORTH ACEH REGENCY - Rina Dara; T. Edyansyah; Rusydi; Syamsul Bahri; Muhammad Roni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research was conducted on the loyalty of make over brand cosmetic products in the people of Panton Labu City, North Aceh Regency. Based on the researcher's observations, consumers have long-term loyalty to makeover brand cosmetics, so that consumers feel that they need the product, feel suitable for the product, and will continue to use the product for an unlimited time. This kind of loyalty shows that customers should always feel satisfied with the product they use for longer and accept the value of the customer experience. This customer assessment is divided into three parts, namely: functional value, emotional value, and social value. Based on the description and problems above, the researcher is interested in conducting a study entitled "The Effect of Customer Experience Value on the Loyalty of Make Over Brand Cosmetic Products in the Community of Panton Labu City, North Aceh Regency". The type of data used in this study is quantitative data, which is data measured in a numerical scale, which measures one or more variables in the population or sample to be studied, both numerically and statistically. The data source used in this study is primary data, namely data obtained directly from respondents or research locations, the coefficient value of the Consumer Response variable (Y) is 0.676 or 67.6%. This value shows that the contribution of the independent variable X1,X2,X3 can explain the Brand Loyalty (Y) variable by 67.6%. Meanwhile, the other 32.4% was influenced by other variables outside the research conducted. Subsequent research could also expand the scope by including other variables that can affect brand loyalty.